Studies in law, politics, and society. Vol. 57 - Sarat, Austin (Bingley, U.K. : Emerald, 2012)
This volume of Studies in Law, Politics, and Society contains an international and interdisciplinary array of legal scholarship. Presenting diverse theoretical perspectives and methodological approaches, this work illuminates the laws response to its social context as well as the way law shapes that context. It shows how legal scholars contribute to public debate about contemporary issues as well as how they articulate the nature of rights and the limits of law.
It's not about race, it's about rights / Ann Sullivan, Valmaine Toki -- Legislative abolition of the death penalty : a qualitative analysis / Kevin H. Wozniak -- The most restrictive alternative : a litigation history of solitary confinement in U.S. prisons, 1960-2006 / Keramet Ann Reiter -- Return of the wrongly convicted : the test for post-conviction executive references in Australia / David Caruso -- Measuring legal formalism : reading hard cases with soft frames / Michal Alberstein -- On law's promise : thinking about how we think about law's limits / Nicky Priaulx.
Keywords: Law -- General; Law -- Indigenous Peoples; Law & society; Legal system: general; Sociological jurisprudence; Political sociology